“Die hart ’n droë blaar”: Verlies, rou en melancholie in Olga Kirsch se Afrikaanse poësie / “The heart a dry leaf”: Loss, Mourning and Melancholia in Olga Kirsch’s Afrikaans Poetry - Viljoen, Louise (Werkwinkel, 2014)
Reading Olga Kirsch’s Afrikaans poetry, one is struck by the important role that the experience of loss occupies in her oeuvre. It is evident in the first two volumes of poetry she published while still living in South Africa, as well as in the five volumes she published after emigrating to Israel in 1948. Because her poetry, especially the volumes written in Israel, exudes an air of melancholy, this article uses Freud’s writings on loss, mourning and melancholia, as well as the historical tradition preceding his work, as a guideline in exploring the way in which the experience of loss, mourning and melancholy is portrayed in Kirsch’s oeuvre. The article focusses on the way in which loss is portrayed in her poetry: her sense that the Jewish experience of loss over the centuries forms part of her history and identity, the way in which she experiences the loss of South Africa and the language Afrikaans in which she is best able to express herself poetically when she emigrates to Israel, the way in which the loss of her father and mother at different times in her life affected her, her feeling that her experience of loss and the ensuing melancholy are carried over to her children.